Comparative Evaluation Of White Wine Production From Different Carbohydrate Rich Substrates Using Air-Lift Bio-Reactor - KARTHIK RAJA.G,; EZHILARASAN .V,; YAZHINI .K.A,; SRIDHAR .S,; CHINNATHAMBI .V, (International Journal of Pharma and Bio Sciences, 2012)
In recent years, wine consumption rate has increased in India. Grapes are used as a primary source in wine production, all over the world. A number of studies have been conducted on apple, guava, banana, jamun, strawberry, apricot, kinnow and plum in order to find an alternate resource. The major objectives of this study are the production of wine using sweet potato and also to find an effective combinational resource. Initially, white wine was produced using sweet potato. Through a detailed analysis, it was confirmed that the rate of white wine production was higher in sweet potato when compare to grapes and figs. Finally, different combinational white wine productions were performed with the help of air-lift bio-reactors. Results suggest that a combination of sweet potato with grapes and sweet potato with beetroot and banana was effective. Anti-microbial activity was carried out in order to verify the fidelity of the produced wine